Dynamics of Business Cycles in Vietnam a Comparison with Indonesia and Philippines - Thanh Ha, Le (Asian Journal of Economics and Empirical Research, 2015)
The main purpose of this paper is to investigate the impacts of structural shocks on macroeconomic fluctuations in Vietnam, and then make a comparison to Indonesia and the Philippines. The study adopts the Structural Vector Autoregressive (SVAR) originated by Shapiro and Watson (1988) and Blanchard and Quah (1989) with long-run restriction for small open-economy with flexibility of price, suggested by Ahmed and Park (1994) and Gali (1992). The evidence for countries suggests that: (i) the main source of output variance is domestic supply shocks but there is a significant decrease in long-run; (ii) the fluctuations of trade balance are mostly due to external shocks, especially term of trade shocks in Vietnam, as opposed to Philippines and Indonesia where IS shocks play an important role; (iii) the fluctuations of real exchange rate are mainly driven by the domestic shocks but internal causes of each country are different; (iv) the two important sources of price’s movements are domestic shocks, especially IS and nominal shocks in Vietnam.